PENGETAHUAN IBU PREMENOPAUSE DENGAN KESIAPAN MENGHADAPI MENOPAUSE DI DUSUN GAMPING KIDUL AMBARKETAWANG GAMPING SLEMAN - Sagitawening, Hardhini; Susanti, Dwi (Universitas Jenderal Achmad Yani Yogyakarta, 2019)
Background: Premenopause is a transitional stage of fertile period leading to the absence of fertilization 4-5 years before menopause. The need for readiness for premenopausal women will affect anxiety in the face of menopause. One of the factors of readiness is knowledge that serves to find out various problems during menopause. Objective: To know the relationship of premenopausal women knowledge with readiness to face menopause at Gamping Kidul, Ambarketawang, Gamping sub district, Sleman Yogyakarta. Methods: Type of quantitative research with cross sectional approach. The population of this study were all premenopausal women aged 45-50 years. The sampling technique used cluster and purposive sampling with research subject of 57 responden. The measuring instrument used was a questionnaire, univariate and bivariate analysis used Kendall's Tau. Results: Good knowledge of premenopausal women 29.8%, sufficient knowledge was 56.1% and lack of knowledge was 14.0% while the category ready 86.0% and not ready 14.0%. The results of statistical tests showed a significant relationship between premenopausal women knowledge and readiness to face menopause (r = 0.647 and p = 0,000). Conclusion : There is a relationship between premenopausal women knowledge with readiness to face menopause at Gamping Kidul, Ambarketawang, Gamping sub district, Sleman Yogyakarta. Keywords: Knowledge, premenopause, readiness